2005
DOI: 10.1037/1076-8998.10.2.97
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Job Characteristics on Work-to-Family Facilitation: Testing a Theory and Distinguishing a Construct.

Abstract: This study used objective measures of job characteristics appended to the National Survey of Midlife Development in the United States (MIDUS), self-reported job characteristics, and an individual resource characteristic (orientation toward personal growth) to test a theory of workfamily facilitation. Results indicated that resource-rich jobs enable work-to-family facilitation. A higher level of work-to-family facilitation was reported by individuals in jobs with more autonomy and variety and whose jobs require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
229
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(264 citation statements)
references
References 49 publications
26
229
1
5
Order By: Relevance
“…Empirical research has indicated a positive relationship between autonomy and WFE (Grzywacz and Butler, 2005).…”
Section: Hypothesis 1a: Autonomy Mediates the Relationship Between Tlmentioning
confidence: 99%
“…Empirical research has indicated a positive relationship between autonomy and WFE (Grzywacz and Butler, 2005).…”
Section: Hypothesis 1a: Autonomy Mediates the Relationship Between Tlmentioning
confidence: 99%
“…Previous studies have indicated that high job demands 10,[14][15][16] and low job control 14,16,17) are positively associated with WFC, which are individual job characteristics in the job-demand-control model 18) . Work-family culture has been found to be negatively associated with WFC 19,20) .…”
Section: Relationship Between Work-related Factors and Wfcmentioning
confidence: 99%
“…Sin embargo, recientemente se ha incorporado una perspectiva que reconociendo que el conflicto existe, propone investigar la interdependencia positiva de los dominios (Greenhaus et al, 2003;Grzywarck, 2002;Frone, 2003). Conceptos tales como enriquecimiento (Kirchmeyer, 1992;Edwards & Rothbard, 2000) y facilitación (Frone, 2003;Grzywacz & Butler, 2005) son algunos ejemplos de planteamientos teóricos que van en la perspectiva de analizar el fenómeno desde un punto de vista propio de la psicología positiva (Seligman, 2002). Así, emerge el concepto de Equilibrio Trabajo-Familia, cuya definición presenta elementos comunes, derivados principalmente de la noción de equilibrio o no equilibrio entre las experiencias en el rol laboral y en el rol familiar (Greenhaus, Collins & Shaw, 2003;Greenhaus & Powell, 2006;Marks & MacDermid, 1996;Kirchmeyer, 2000;Clark, 2000).…”
Section: Concepto De Satisfacción Familiar Y Equilibrio Trabajo-familiaunclassified
“…Frone (2003) y Greenhaus & Powell, (2006) definen el enriquecimiento como una situación donde las experiencias, habilidades y oportunidades desplegadas en un dominio (familiar o laboral), mejoran o afectan la calidad de vida en el otro. La facilitación trabajo-familia presenta interesantes líneas de investigación en relación a cómo las organizaciones promueven la relación trabajofamilia y si el equilibrio trabajo y familia es igualmente importante para hombres que para mujeres (Grzywacz & Butler, 2005). Por ejemplo, componentes de facilitación trabajo-familia, medidas por las facilidades percibidas en el lugar de trabajo para ocuparse de asuntos personales y familiares, o las posibilidades de transferir las habilidades usadas en el ámbito laboral al ámbito familiar, han sido correlacionados con bienestar físico y mental (Grzywacz & Bass, 2003), así como mayores niveles de satisfacción organizacional y familiar (Wayne, Musisca & Fleeson, 2004).…”
Section: Concepto De Satisfacción Familiar Y Equilibrio Trabajo-familiaunclassified